Gestao de risco das principais tesourarias de fundos de investimento em ações no Brasil - Ferreira, Antonio Glênio Moura (2014)
This study aims to examine empirically the behavior of the model for measuring market risk Value at Risk - VaR in its parametric interpretation unconditional Gaussian and extensions that regulate violations on heteroscedasticity and non-normality of daily returns of investment funds Actions, of the thirteen largest financial institutions resident in Brazil, during the January/06 dezembro/12. For a better evaluation of the data, we sought to initially model the conditional evolution of risk and adjust the statistic al idiosyncrasy of temporal series of thirteen treasuries, using probability distributions that best adapt to the analysis of the models. The results obtained with the semodels are analyzed by the test failure rate proposed by Kupiec (1995) and Chisttoffersen (1998). The survey also shows, with graphic examples, a performance Risk - Return of the thirteen banks using the methodology proposed by Balzer.